Governor's Residence, Trinidad, B.W.I. - (:unkn) unknown (Ace Studio, Trinidad, 2009)
A picture of the Governor's residence with its Italian style arched doorways, Victorian style columns and railings and walls of local blue limestone. Today this residence is known as "The President's House". Postcard number 10.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Architecture--Trinidad and Tobago; President's House, The